Effectiveness of the Two-in-One Device; Ignition Coil and Spark Plug Testing Instrument - Guillermo, Allan Q.; Bajet, Jr., Manuel A.; Tolentino, Dominador F. (JPAIR Multidisciplinary Research, 2015)
Technological modernization and invention have brought convenience that life has become fulfilling, and they give amusement to our lives. This study aimed to evaluate the effectiveness of the Ignition Coil and Spark Plug Instrument that can be used to determine the condition of an Ignition coil through high voltage output and also spark plug through visible spark. It made use of project and experimental method of research. This was accomplished in three phases namely: the making of the design for the device, constructing the device and testing the device functionality through actual observation. Group of experts coming from the automotive and electronic sectors evaluated the effectiveness of the automotive testing instrument. A five-point Likert scale was used to find the mean product and the descriptive rating in terms of usefulness, effectives, functionality, reliability and safety. The results of the study revealed that the output voltage and frequency are directly proportional to the resistance of network Ra, but inversely proportional to resistance network Rb in the circuit.Â The output frequency is directly proportional to the output voltage. The evaluation of the group of experts in terms of usefulness, effectiveness, functionality, reliability and safety was rated excellent respectively. The device is an instrument for automotive technicians in testing ignition coil and spark plugs. The researchers recommended further study about the device for its safety because based on the result it has the least rating among the different standards although it was evaluated as â€œExcellent.â€ Â Â Â Â Â Â Â Â Â Â Â Keywords â€“ Engineering, development, ignition, spark plug, testing instrument, R and D, Vigan City, Philippines